Strain‐Promoted 1, 3‐Dithiolium‐4‐olates–Alkyne Cycloaddition. (3rd September 2019) - Kumar, Ramar Arun; Pattanayak, Manas R.; Yen‐Pon, Expédite; Eliyan, Jijy; Porte, Karine; Bernard, Sabrina; Riomet, Margaux; Thuéry, Pierre; Audisio, Davide; Taran, Frédéric
Abstract: Reported here is the reactivity of mesoionic 1, 3‐dithiolium‐4‐olates towards strained alkynes, leading to thiophene cycloaddition products. In the process, the potential of these dipoles towards orthogonal reaction with azides, allowing efficient double ligation reactions, was discovered. A versatile process to access benzo[c]thiophenes, in an unprecedented divergent fashion, was developed and provides a new entry to unconventional polyaromatic thiophenes. Abstract : Unter Spannung : 1, 3‐Dithiolium‐4‐olate reagieren mit gespannten Alkinen, was polyaromatischen Thiophenstrukturen in hohen Ausbeuten ergibt. Ihr Nutzen für Ligationsanwendungen wurde mit Cyclooctinen untersucht, was eine neue orthogonale Reaktion zur spannungsvermittelten Azid‐Alkin‐Reaktion liefert.